2015
DOI: 10.1038/srep17476
|View full text |Cite
|
Sign up to set email alerts
|

Effects of histamine H1 receptor signaling on glucocorticoid receptor activity. Role of canonical and non-canonical pathways

Abstract: Histamine H1 receptor (H1R) antagonists and glucocorticoid receptor (GR) agonists are used to treat inflammatory conditions such as allergic rhinitis, atopic dermatitis and asthma. Consistent with the high morbidity levels of such inflammatory conditions, these receptors are the targets of a vast number of approved drugs, and in many situations their ligands are co-administered. However, this drug association has no clear rationale and has arisen from clinical practice. We hypothesized that H1R signaling could… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
27
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
4
1

Relationship

3
2

Authors

Journals

citations
Cited by 14 publications
(28 citation statements)
references
References 46 publications
1
27
0
Order By: Relevance
“…We first validated that AZE had similar effect on DEX‐induced GR transcriptional activity in vitro , as previously reported for the antihistamines mepyramine and triprolidine . HEK293T cells were cotransfected with a luciferase encoding plasmid under the control of a synthetic promoter regulated by the GR (TAT3‐Luc) in combination with plasmids encoding for GR and H 1 receptor.…”
Section: Resultsmentioning
confidence: 54%
See 3 more Smart Citations
“…We first validated that AZE had similar effect on DEX‐induced GR transcriptional activity in vitro , as previously reported for the antihistamines mepyramine and triprolidine . HEK293T cells were cotransfected with a luciferase encoding plasmid under the control of a synthetic promoter regulated by the GR (TAT3‐Luc) in combination with plasmids encoding for GR and H 1 receptor.…”
Section: Resultsmentioning
confidence: 54%
“…As shown before, no differences were observed in results normalized to Renilla-Luc or to protein expression levels. 4 EXP-FYB N° 0040903/2015) and were performed in accordance with institutional and national guidelines for animal protection. Animal studies are reported in compliance with the ARRIVE guidelines.…”
Section: Transfection and Reporter Gene Assaysmentioning
confidence: 99%
See 2 more Smart Citations
“…This clinical practice has been stablished based on the assumption that there should be an intrinsic benefit in their coadministration due to their antiinflammatory effects. 26 It has been shown that the combination of antihistamines and corticoids is the most widely used choice to treat all types of AR. 27 Several clinical trials have shown the benefits of the combination of the antihistamine azelastine (AZE) and the corticoid fluticasone (FLU), resulting in the patent granting of the first steroid plus antihistamine nasal spray (Dymista®) along with two other steroid combinations.…”
Section: Antihis Tamine S and G Luco Corti Coidsmentioning
confidence: 99%